Prevalence of undernutrition among pregnant women and its differences across relevant subgroups in rural Ethiopia: a community-based cross-sectional study - Nana Chea; Yadessa Tegene; Ayalew Astatkie; Mark Spigt (BMC, 2023)
Key message Undernutrition is a highly prevalent problem among rural Ethiopian pregnant women, especially with those who avoid food/s, do not get counseled, and had two or more pregnancies and a history of miscarriage. All healthcare providers, especially those working in ANC and child services in Ethiopia, should be aware of the risks of maternal undernutrition. Nutritional education and counseling at the ANC clinic should be strengthened, and there should be reinforcement mechanisms